Air pollution study of vehicles emission in high volume traffic: Selangor, Malaysia as a case study - Ahmad Shuhaili, Ahmad Fadzil; Ihsan, Sany Izan; Faris, Waleed Fekry (World Scientific and Engineering Acadddemy and Society (WSEAS), 2013)
In an internal combustion engine, a chemical reaction occurs between the oxygen in air and hydrocarbon fuel. Engines operate at what is termed the stoichiometric air/fuel ratio when there is the correct quantity of air to allow complete combustion of the fuel with no excess oxygen. In reality, the combustion process cannot be perfect and automotive engines emit several types of pollutants.Therefore, it is important to develop and deploy methods for obtaining real-world, on-road micro-scaled measurements of vehicle emissions to estimate the pollutants. In this work, several high traffic roads in Selangor will be selected for the road airquality measurement and analysis. Comparisons with simulations results, using the Operational Street Pollution Model (OSPM) are shown. The study shows that there were no serious of air pollution recorded in the period of January 2012. Air quality trends for the criteria pollutants in this month generally are continuing to show downward trends or stable trends well below the level of the Malaysian Ambient Air Quality Guideline (RMG). However, PM10 and ground-level O3 are the crucial pollutants in Selangor. The comprehensive review has revealed that moving vehicles creates a significant impact in air quality on the specific locations. Comparison with simulated data also showed good agreement thus indicating suitability of the model to be used in Malaysia condition.